The migration of professionals within the EU: any barriers left? - Capuano, Stella; Migali, Silvia (Nürnberg, 2016)
"Despite the effort at EU level to harmonize the process of recognition of foreign educational qualifications, the European states differ in their propensity to accept high-school and academic certificates obtained in other EU member states. In turn, a country's higher degree of recognition of foreign qualifications might be an attractor of non-native skilled workers. We provide evidence on this issue using new data on the outcome of the recognition process in every EU country. Estimating different panel data gravity models, we find that the migration rate to a given destination country is positively affected by its propensity to recognize foreign educational qualifications."